ENHANCING STUDENT ENGAGEMENT AND READING IN NARRATIVE LITERACY WITH QUICK MAKER - Marpaung, Syafaruddin (SEAMEO QITEP in Language, 2025)
This Classroom Action Research (CAR) study investigates the impact of the Quick Maker method (Quizizz Cara Kertas Memakai Atribut Kemerdekaan dan Stiker) on student engagement and narrative text literacy. Conducted with 34 students from one class at a senior high school in Tanjungbalai, data were collected through questionnaires, interviews, and observations. The research followed Stringer's (2007)